Transcription factors in light and circadian clock cignaling networks revealed by genomewide mapping of direct targets for neurospora white collar complex - Smith, Kristina M.; Sancar, Gencer; Dekhang, Rigzin; Sullivan, Christopher M.; Li, Shaojie; Tag, Andrew G.; Sancar, Cigdem; Bredeweg, Erin L.; Priest, Henry D.; McCormick, Ryan F.; Thomas, Terry L.; Carrington, James C.; et al. (Eukaryotic cell, 2010)
Light signaling pathways and circadian clocks are inextricably linked and have profound effects on behavior in most organisms. Here, we used chromatin immunoprecipitation (ChIP) sequencing to uncover direct targets of the Neurospora crassa circadian regulator White Collar Complex (WCC). The WCC is a blue-light receptor and the key transcription factor of the circadian oscillator. It controls a transcriptional network that regulates ∼20% of all genes, generating daily rhythms and responses to light. We found that in response to light, WCC binds to hundreds of genomic regions, including the promoters of previously identified clock- and light-regulated genes. We show that WCC directly controls the expression of 24 transcription factor genes, including the clock-controlled adv-1 gene, which controls a circadian output pathway required for daily rhythms in development. Our findings provide links between the key circadian activator and effectors in downstream regulatory pathways.
Gesehen am 09.08.2023